Oltre la zona di interesse. Un’analisi della responsabilità nel presente tra Glazer e Levinas - Bottacin Cantoni, Lorenza (Filosofia Morale/Moral Philosophy, 2024)
This paper explores the question of historical memory and ethical responsibility through an analysis of Jonathan Glazer’s film “The Zone of Interest” and Levinas’ philosophical reflections on the ethics of responsibility and disinterestedness. The film is interpreted as a critical reflection on modern man’s ability to distinguish good from evil in a world normalized by evil itself. Through the specific use of images, sounds, and montages, Glazer invites reflection on individual responsibility for history and perpetuated evil, proposing an antithesis to an “anesthetized memory” that merely remembers without acting. The article analyzes how the film proposes a new kind of being in the world, one in which Levinas’s disinterestedness becomes an antidote to the passive acceptance of horror and stimulates an active responsibility toward the other, a critical engagement that transforms memory into a duty of justice and ethical action.